2018
DOI: 10.1093/gji/ggy470
|View full text |Cite
|
Sign up to set email alerts
|

On-site earthquake early warning: a partially non-ergodic perspective from the site effects point of view

Abstract: We introduce in the on-site earthquake early warning (EEW) a partially non-ergodic perspective from the site effects point of view. We consider the on-site EEW approach where the peak ground velocity (PGV) for S waves is predicted from an early estimate, over the P waves, of either the peak-displacement (PD) or cumulative squared velocity (IV2). The empirical PD-PGV and IV2-PGV relationships are developed by applying a mixed-effect regression where the site-specific modifications of ground shaking are treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…Nevertheless, the full investigation and explanation of the causes of these site conditions is beyond the aim of this paper. In our opinion, the significant variation in residuals shown in Figure 5A is not surprising, being in agreement with other studies (Spallarossa et al, 2019;Iaccarino et al, 2020); which have recently discussed how to reduce the prediction variability considering site-effect terms in EEW model using the mixed-effect regression approach (Pinheiro and Bates, 2000).…”
Section: Residual Analysissupporting
confidence: 92%
See 2 more Smart Citations
“…Nevertheless, the full investigation and explanation of the causes of these site conditions is beyond the aim of this paper. In our opinion, the significant variation in residuals shown in Figure 5A is not surprising, being in agreement with other studies (Spallarossa et al, 2019;Iaccarino et al, 2020); which have recently discussed how to reduce the prediction variability considering site-effect terms in EEW model using the mixed-effect regression approach (Pinheiro and Bates, 2000).…”
Section: Residual Analysissupporting
confidence: 92%
“…In other words, models calibrated combining datasets from different regions are exported to further areas assuming that regional effects do not play role in the model uncertainty (Stafford, 2014). However, results of recent EEW studies (e.g., among others Spallarossa et al, 2019;Iaccarino et al, 2020) have shown the opposite; that is to say, regional characteristics can play an important role in the robustness and accuracy of the EEW predictions, leading to increase the epistemic uncertainty (Al Atik et al, 2010). For this reason, we proceeded setting four different case studies using datasets of increasing order of heterogeneity.…”
Section: Case Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the idea was first proposed by Cooper in the mid-19th century [1], EEW systems have only been realized in recent decades thanks to advances in communications, digital seismology, and automatic processing [2]. The development and implementation of EEW systems were summarized in previous studies by Allen et al [3] and Allen and Melgar [4], and it is still an emerging research topic in the community [5][6][7][8][9]. The EEW systems could also incorporate with structural control algorithms for better seismic response reduction [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies (e.g. Festa et al 2008;Picozzi et al 2018;Spallarossa et al 2019) propose to incorporate the early radiated energy, obtained as the squared velocity integrated over time. As the quantitative results in these studies are obtained in the context of early warning, they can not directly be compared to the results of this study.…”
Section: Multifeature Magnitude Estimation 143 1 Introductionmentioning
confidence: 99%